THE ROLE OF BRAIN CENTERS IN SPEECH PERCEPTION AND PROCESSING (Universal International Scientific Journal, 2026)
This scientific article comprehensively analyzes the neurophysiological basis of speech perception and development processes. Speech activity is carried out as a result of specialized areas of the cerebral cortex, subcortical structures and their mutual functional integration. In particular, Broca's area and Wernicke's area, located in the left hemisphere, provide the expressive and impressionistic aspects of speech, respectively. The role of the arcuate fasciculus, motor cortex, auditory cortex and limbic system in the speech process is also highlighted. The article describes a systematic model of speech based on classical localization theories and the results of modern neuroimaging studies. Types of aphasia, their clinical symptoms and neuropsychological diagnostic issues are also considered.
Keywords: speech; neuropsychology; Broca's area